2020
DOI: 10.1155/2020/6458060
|View full text |Cite
|
Sign up to set email alerts
|

PERK Overexpression-Mediated Nrf2/HO-1 Pathway Alleviates Hypoxia/Reoxygenation-Induced Injury in Neonatal Murine Cardiomyocytes via Improving Endoplasmic Reticulum Stress

Abstract: Reperfusion processes following acute myocardial infarction (AMI) have been reported to induce additional cardiomyocyte death, known as ischemia-reperfusion (I/R) injury. Endoplasmic reticulum (ER) stress is reported to be involved in the development of I/R injury. There is evidence that PERK exerts beneficial roles in alleviating ER stress. Here, we investigated whether upregulation of PERK improved cardiomyocytes injury induced by I/R. Specific siRNAs or adenovirus vectors were incubated with isolated neonat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 36 publications
(40 reference statements)
0
14
0
Order By: Relevance
“…In various preclinical ischemia and reperfusion experimental models, it has been demonstrated the downregulation of Nrf2 and associated antioxidant genes expression in cardiac tissue (Silva‐Palacios et al, 2019; Yang, Ding, et al, 2020; Yang, Liu, et al, 2020; Yang, Mao, et al, 2020; Zhao et al, 2020; Zhao, Chen, Wang, & Cai, 2020; Zheng et al, 2020). Recently, Wang et al (2020) demonstrated that the silensing of the gene, Nrf2 or HO‐1 reduces the viability of neonatal cardiomyocytes isolated from neonatal mice following hypoxia/reoxygenation. They found that upregulation of Nrf2/HO‐1 (through protein kinase‐like endoplasmic reticulum kinase overexpression) reduces the expression of endoplasmic reticulum stress related pro‐apoptotic markers, GRP78, CHOP, calreticulin (CRT) and caspase‐12 in neonatal cardiomyocytes following hypoxia/reoxygenation, and prevents the cardiomyocytes death (Wang et al, 2020).…”
Section: Herbal Nrf2 Activator and Cardiovascular Diseasesmentioning
confidence: 99%
“…In various preclinical ischemia and reperfusion experimental models, it has been demonstrated the downregulation of Nrf2 and associated antioxidant genes expression in cardiac tissue (Silva‐Palacios et al, 2019; Yang, Ding, et al, 2020; Yang, Liu, et al, 2020; Yang, Mao, et al, 2020; Zhao et al, 2020; Zhao, Chen, Wang, & Cai, 2020; Zheng et al, 2020). Recently, Wang et al (2020) demonstrated that the silensing of the gene, Nrf2 or HO‐1 reduces the viability of neonatal cardiomyocytes isolated from neonatal mice following hypoxia/reoxygenation. They found that upregulation of Nrf2/HO‐1 (through protein kinase‐like endoplasmic reticulum kinase overexpression) reduces the expression of endoplasmic reticulum stress related pro‐apoptotic markers, GRP78, CHOP, calreticulin (CRT) and caspase‐12 in neonatal cardiomyocytes following hypoxia/reoxygenation, and prevents the cardiomyocytes death (Wang et al, 2020).…”
Section: Herbal Nrf2 Activator and Cardiovascular Diseasesmentioning
confidence: 99%
“…Acute myocardial infarction (AMI) is one of the leading causes of mortality in patients with cardiovascular disease worldwide ( 1 ), accounting for 80% of cardiogenic shock ( 2 ). AMI is caused by coronary artery blockage and myocardial ischemic necrosis, which eventually leads to heart failure ( 3 ). Therefore, early reperfusion therapy can save the dying myocardium, which is essential for blood supply and nutritional support of ischemic myocardium, as well as improving the prognosis of patients with AMI ( 1 , 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…AMI is caused by coronary artery blockage and myocardial ischemic necrosis, which eventually leads to heart failure ( 3 ). Therefore, early reperfusion therapy can save the dying myocardium, which is essential for blood supply and nutritional support of ischemic myocardium, as well as improving the prognosis of patients with AMI ( 1 , 3 ). However, there is evidence that traditional reperfusion therapy can cause additional damage to myocardial structure and function, namely myocardial ischemia-reperfusion injury (IRI) ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations